Nicholas King family papers - King, N. (Nicholas), 1771-1812.; Wade, Nicholas King, 1823-1899.; Wade, William, 1789-1875.
Papers of Nicholas King consist largely of journals (1793-1799) and transcribed excerpts from journals (1792-1811) describing travels in England; his voyage to America and first impressions there, particularly in Philadelphia and Pennsylvania; and his work as a surveyor and overseer of the construction of federal buildings in Washington, D.C. Also includes transcripts of letters from King and his father, Robert King, also an engineer and surveyor; drawings; sketches; and photographs. Papers of William Wade include a letter to his son, Nicholas King Wade; correspondence (1861) with Mark A. Cooper regarding a test for the strength of iron; visas; and a memorandum relating to his participation in an inspection tour, sponsored by the U.S. War Dept., of European cannon factories in 1840. Papers of Nicholas King Wade consist of letters (1856) to his sister, Elizabeth Stone Wade, describing his journey from Berlin, Germany, to Saint Petersburg, Russia, where he had a contract with the Russian government to manufacture ordnance. Also includes genealogies of the King and Wade families compiled in the 1980s.
Family of Nicholas King, English-born engineer and surveyor of the city of Washington, D.C., including his son-in-law, Maj. William Wade, U.S. Army ordnance officer and, later, part owner of a series of steam engine and cannon foundries in Pittsburgh, Pa., and his grandson, Nicholas King Wade, engineer and foundry owner.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cooper, Mark A. -- 1800-1885 -- Correspondence; King, Robert, -- 1740-1817 -- Correspondence; Wade, Elizabeth Stone, -- 1840-1913 -- Correspondence; King family; Wade family; United States. -- Army -- Ordnance and ordnance stores; United States. -- War Department; Architecture -- Washington (D.C.); Arsenals -- Europe; Iron; Iron industry -- Pennsylvania -- Pittsburgh; Ordnance -- Europe; Ordnance -- Russia; Public buildings -- Washington (D.C.); Surveying -- Washington (D.C.); Voyages and travels; Berlin (Germany) -- Description and travel; England -- Description and travel; Pennsylvania -- Description and travel; Philadelphia (Pa.) -- Description and travel; Saint Petersburg (Russia) -- Description and travel; Engineers; Surveyors